Preserving the scientific and technical Heritage of Education: the ASEISTE - Gires, Francis; Lauginie, Pierre (Museologia e Patrimônio, 2014)
ASEISTE, Association de sauvegarde et d’étude des instruments scientifiques et techniques de l’enseignement, is a French association aiming at the preservation and study of the scientific and technical instruments of Education, especially in secondary education schools. The main achievements of the Association are described in this paper, specially: the website and its comprehensive catalogue of more than 4000 objects, the videos, the books and exhibitions devoted to important collections. The paper includes numerous photographs of typical objects. Finally, projects are evoked and a call is launched for exchange of informations and cooperation with similar institutions from abroad.